Comparison of the standing balance between pole vaulters and soccer players in preseason and postseason - Dmitruk, K.; Galazka, M.; Cieslicka, M.; Soszynski, D.; Stepniak, R.; Klimczyk, M.; Iermakov, S. S. (Physical Education of Students, 2020)
Background and Study Aim: Static is crucial in the maintaining the position of the body`s center of gravity vertically over the base of support. Many sport disciplines require effective balance system. However, the efficiency of the system differs based on the sport discipline. The aim of the study was to examine balance system efficiency in pole vaulters and soccer players. Additionally, the analysis of pre and postseason balance system efficiency was performed in pole vaulters and soccer players as well. Material and Methods: To asses static balance system efficiency five pole vaulters and six soccer players were examined. A balance platform was used for open eyes test, close eyes test and biofeedback test. During the tests displacements of the center of pressure (COP) and calculates parameters such as: sway area in mm2 (P), mean total length in mm (L), path length in antero-posterior plane in mm (LA-P), path length in medio-lateral plane in mm (LM-L) and coordination in % (C) were obtained. Results: Pole volunteers displayed better static balance and coordination compared to soccer players both in postseason and preseason time. Static balance and coordination were better in preseason compared to postseason time in pole vaulters. The observed differences were not statistically significant. Soccer players exhibited lower balance scores (statistically significant) in preseason compared to postseason. The eyes closure resulted in increased values of both total sway length, sway length in AP plane and sway length in ML plane both in postseason and preseason time for both groups of athletes. Intercondition significance was assessed only for total sway length and sway length in AP plane in pole vaulters in postseason time. Conclusions: Pole vaulters and soccer players did not differ in terms of static balance, but our results point toward an overall tendency for pole vaulters to exhibit better standing balance and visual-motor coordination compared soccer players.